2014
DOI: 10.1017/jfm.2014.193
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-based adaptive simulations of three-dimensional flow past a square cylinder

Abstract: The wavelet-based eddy capturing approach is extended to three-dimensional bluff body flows, where the flow geometry is enforced through Brinkman volume penalization. The wavelet-collocation/volume-penalization combined method is applied to the simulation of vortex shedding flow behind an isolated stationary prism with square cross-section. Wavelet-based direct numerical simulation is conducted at low supercritical Reynolds number, where the wake develops fundamental three-dimensional flow structures, while wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…While WA-LES is not predicated on a specific class of closure procedures, certain SGS modelling properties are particularly advantageous in this framework. By employing models that automatically switch off in well-resolved flow regions, the control of the overall physical fidelity can be achieved by means of the adaptive wavelet-based filtering procedure (De Stefano & Vasilyev 2014), thereby forming a completely unified eddy-resolving modelling framework, capable of continuously changing between WA-LES, CVS and wavelet-based adaptive direct numerical simulation (WA-DNS) regimes, within a single simulation. The filtering parameters can be automatically adjusted, both spatially and temporally, based on objective physically based criteria throughout the course of the simulation, while targeting specific flow phenomena, which leads to the intelligent simulation of turbulent flows (Nejadmalayeri et al 2014; De Stefano, Nejadmalayeri & Vasilyev 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While WA-LES is not predicated on a specific class of closure procedures, certain SGS modelling properties are particularly advantageous in this framework. By employing models that automatically switch off in well-resolved flow regions, the control of the overall physical fidelity can be achieved by means of the adaptive wavelet-based filtering procedure (De Stefano & Vasilyev 2014), thereby forming a completely unified eddy-resolving modelling framework, capable of continuously changing between WA-LES, CVS and wavelet-based adaptive direct numerical simulation (WA-DNS) regimes, within a single simulation. The filtering parameters can be automatically adjusted, both spatially and temporally, based on objective physically based criteria throughout the course of the simulation, while targeting specific flow phenomena, which leads to the intelligent simulation of turbulent flows (Nejadmalayeri et al 2014; De Stefano, Nejadmalayeri & Vasilyev 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A few authors have considered the low-Mach-number regime of compressible transport equations, for instance, investigating CVS of mixing layers (Roussel & Schneider 2010). Furthermore, research has been limited to a relatively narrow set of configurations, including homogeneous isotropic turbulence (Goldstein et al 2005; De Stefano & Vasilyev 2010), as well as turbulent wake flows behind bluff bodies (De Stefano & Vasilyev 2014; De Stefano et al 2016). Though the latter feature bounded flows, the Reynolds number was in the transitional regime and the boundary layer remained laminar.…”
Section: Introductionmentioning
confidence: 99%
“…Early simulations based upon the velocity‐vorticity formulation were presented by Fröhlich and Schneider . While more general adaptive collocation techniques were put forth by Vasilyev and Kevlahan, more recently, adaptive wavelet methods have seen use in conjunction with lattice Boltzmann and penalty methods to treat complex geometries . A detailed review on the application of wavelets to turbulent flows may be found within the work of Schneider and Vasilyev …”
Section: Introductionmentioning
confidence: 99%
“…36 While more general adaptive collocation techniques were put forth by Vasilyev and Kevlahan, 37 more recently, adaptive wavelet methods have seen use in conjunction with lattice Boltzmann and penalty methods to treat complex geometries. 38,39 A detailed review on the application of wavelets to turbulent flows may be found within the work of Schneider and Vasilyev. 40 In contrast to the prior works, our purpose for the SGW is unique, as we would like to make use of the SGW, solely to enhance the quality of the scale separation in the three-scale VMS-LES procedure.…”
mentioning
confidence: 99%
“…It dynamically adapts the grid using a wavelet basis decomposition to track localized structures in the solution, exploiting spatio-temporal intermittency to optimize the total grid point count. As a result, AWCM has been used to effectively analyze many physical problems, including turbulence [5,6,7], reacting flows [8,9], and geophysics [10].…”
Section: Introductionmentioning
confidence: 99%